De novo and inherited micro-CNV at 16p13.11 in 21 Chinese patients with defective cardiac left-right patterning - Yu, Kun; Chen, Weicheng; Chen, Yan; Shen, Libing; Wu, Boxuan; Zhang, Yuan; Zhou, Xiangyu (Frontiers in Genetics, 2024)
Copy number changes at Chromosomal 16p13.11 have been implicated in a variety of human diseases including congenital cardiac abnormalities. The clinical correlation of copy number variants (CNVs) in this region with developmental abnormalities remains controversial as most of the patients inherit the duplication from an unaffected parent.We performed CNV analysis on 164 patients with defective left-right (LR) patterning based on whole genome-exome sequencing (WG-ES) followed by multiplex ligation-dependent probe amplification (MLPA) validation. Most cases were accompanied with complex congenital heart disease (CHD).Results: CNVs at 16p13.11 were identified in a total of 21 cases, accounting for 12.80% (21/164) evaluated cases. We observed a marked overrepresentation of chromosome 16p13.11 duplications in cases when compared with healthy controls according to literature reports (15/164, 9.14 % versus 0.09 % in controls). Notably, in two independent family trios, de novo 16p13.11 micro-duplication were identified in two patients with laterality defects and CHD. Moreover, 16p13.11 micro-duplication was segregated with the disease in a family trio containing 2 affected individuals. Notably, five coding genes, NOMO1, PKD1P3, NPIPA1, PDXDC1 and NTAN1, were potentially affected by micro-CNV at 16p13.11 in these patients.Our study provide new family-trio based evidences to support 16p13.11 micro-duplications predispose individuals to defective cardiac left-right patterning and laterality disorder.